Penerapan Model Problem Based Learning untuk Meningkatkan Proses Pembelajaran Tematik Terpadu Kelas IV Sekolah Dasar - Putra, Beni Andika; Desyandri, Desyandri (Universitas Negeri Padang, 2021)
This study aimed to describe the increase of students learning outcome on thematic integrated learning using PBL. This research was classroom action research with qualitative and quantitative approaches. The participants of this research were teacher and 22 students of SDN 23 Marapalam Padang City. The results showed: 1. Lesson plan assessment in cycle I was 78.12% then increased to 93.75% in cycle II. Observation on teacher aspect in cycle I was 85.71% and went up to 96.42% in cycle II while on aspect of students in cycle I was 85.71% the increased to 96.42% in cycle II. Affective aspect of students, the were 5 student who showed caring, honestly in cycle I. It increased to 8 students in cycle II. Cognitive aspect, in cycle I was 77.27 then went up to 89.51 in cycle II. In psychomotor aspect in cycle I was 76.70 and increased 83.80 in cycle II. It can be increased the students learning outcomes on thematic integrated learning.